E-Learning Based on Video Presentations to Enhances Attitudes, Skills, and Pedagogical Knowledge of Prospective Teacher Students During the Covid-19 Pandemic - Murtafiah, Wasilatul; Krisdiana, Ika; Masfingatin, Titin; Susanti, Vera Dewi; Setyansah, Reza Kusuma (Jurnal Pendidikan Indonesia, 2021)
This study aims to develop an e-learning tool based on video presentations to enhances attitudes, skills and pedagogical knowledges of prospective teacher students during the Covid-19 pandemic. This type of research is Research and Design (R & D) using the Plomp development model, which consists of 3 stages: a preliminary study, design, and assessment. Data collection was carried out through observation, device validation, distribution of response questionnaires, and assessment of student learning outcomes. The results of the data analysis show that at the preliminary study stage, it was found that there were still no devices that supported learning during the Covid-19 pandemic. At the stage of design was designed, including RPS, LMS Settings, and Video Presentations. At the assessment stage, it was found that all the tools developed had valid criteria, students gave a positive response to the small and broad trials respectively of 97.68%; 98.32% so that the tools developed were included in practical criteria. The assessment of learning outcomes in the aspects of attitudes, skills, and knowledge had average completeness on the small and broad trials respectively of 82.92%; 86.99% so that the equipment used was included in the effective criteria. Thus the device developed can be said to be feasible because it meets the criteria of validity, practicality, and effectiveness. The development of e-learning based on video presentations can be used to enhance attitudes, skills, and pedagogical knowledge of prospective mathematics teacher students.